Investigating the Prospective Sense of Agency: Effects of Processing Fluency, Stimulus Ambiguity, and Response Conflict - Sidarus, Nura; Vuorre, Matti; Metcalfe, Janet; Haggard, Patrick (Frontiers in Psychology, 2017)
How do we know how much control we have over our environment? The sense of agency refers to the feeling that we are in control of our actions, and that, through them, we can control our external environment. Thus, agency clearly involves matching intentions, actions, and outcomes. The present studies investigated the possibility that processes of action selection, i.e., choosing what action to make, contribute to the sense of agency. Since selection of action necessarily precedes execution of action, such effects must be prospective. In contrast, most literature on sense of agency has focussed on the retrospective computation whether an outcome fits the action performed or intended. This hypothesis was tested in an ecologically rich, dynamic task based on a computer game. Across three experiments, we manipulated three different aspects of action selection processing: visual processing fluency, categorization ambiguity, and response conflict. Additionally, we measured the relative contributions of prospective, action selection-based cues, and retrospective, outcome-based cues to the sense of agency. Manipulations of action selection were orthogonally combined with discrepancy of visual feedback of action. Fluency of action selection had a small but reliable effect on the sense of agency. Additionally, as expected, sense of agency was strongly reduced when visual feedback was discrepant with the action performed. The effects of discrepant feedback were larger than the effects of action selection fluency, and sometimes suppressed them. The sense of agency is highly sensitive to disruptions of action-outcome relations. However, when motor control is successful, and action-outcome relations are as predicted, fluency or dysfluency of action selection provides an important prospective cue to the sense of agency.